Avaliação de serviços ecossistêmicos em áreas verdes e florestas urbanas: um protocolo de avaliação rápida para cidades - Barbosa, Valéria Letícia Marques (Universidade Federal de São Carlos, 2024)
Urban green areas provide ecosystem services, benefits people obtain from ecosystems, which are clustered in four categories: Cultural, Provisioning, Regulating and Supporting. Researchers have created and tested some protocol to assess ecosystem services in urbanised areas of temperate regions; nevertheless, development countries lack studies, notwithstanding their distinct environmental and social realities. Hence, this master's program objective to propose an instrument that any development-country technician is able to use simply, rapidly, but still sensitively. As different green areas possess different potentials to deliver ecosystem services, according to their properties and goals, the protocol must assess ES, evaluating weaknesses and strengths for each area. First, a systematic literature review was carried out to assess theme's state of art, according to PRISMA method. Subsequently, ES indicators were selected to assess the four categories; they ought to be sensitive, user-friendly, and adapted to urban environments. Indicators were ranked in four grades which represented the ES supply quality in the area: I- extremely unsatisfactory, II- unsatisfactory, III- satisfactory and IV- extremely satisfactory. Empirical tests to calibrate the protocol and assess each ES supply were performed in autumn, in the city of Sorocaba. Areas comparison demonstrated the protocol is sensitive to identify differences amongst areas, and may serve as a management instrument for municipal environmental secretaries. Finally, it is pointed out that urban green areas may attend, with proper planning, a multitude of benefits for the population on several fronts. Thus, areas which embrace social and environmental elements combined stand out with the most complete offer of ES and well-being.
Ecosystem services assessment in urban green areas and urban forests: rapid assessment protocol for cities
Keywords: planejamento verde urbano; infraestrutura verde; índice de serviços ecossistêmicos; urban green planning; green infrastructure; ecosystem services index; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL::TECNICAS DE PLANEJAMENTO E PROJETO URBANOS E REGIONAIS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS FISICO-AMBIENTAIS DO PLANEJAMENTO URBANO E REGIONAL